Problematika Dan Strategi Pembelajaran Bahasa Indonesia Di Sekolah Dasar Swasta At-Taufiq Kelas Rendah - Jean Emeninta Surbakti; Nia Afrilda Nasution; Imam Sholeh Rambe; Hana Br Sinaga; Khairunnisa Khairunnisa (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Learning Indonesian in elementary schools, especially in lower grades, faces various obstacles. This problem includes student learning outcomes that have not reached the Minimum Completeness Criteria (KKM) and monotonous teaching methods. This study aims to explore the obstacles teachers face during learning and the strategies they use at At-Taufiq Private Elementary School. The data collection method involved interviews with class I, II, and III teachers. The findings show that the direct learning strategies used, such as the lecture method, are not effective because they make students feel bored. Alternative strategies such as the use of learning media such as storybooks and infocus are recommended to increase students' interest in learning. This research aims to explore the obstacles faced in learning Indonesian in the lower grades of At-Taufiq Private Elementary School and identify effective learning strategies to overcome these problems. Thus, this research aims to identify learning obstacles and provide innovative solutions to improve quality. Indonesian language learning in elementary schools.